Advances in Islamic Finance, Marketing, and Management: An Asian Perspective. - Mutum, Dilip (Online access with EBA: Emerald Business, Management & Economics., 2016)
Of interest to both academics and practitioners who assist in making Shariah-centric strategies, this work is particularly important as Asia holds a major percentage of Islamic assets in South Asia, Southeast Asia, and the Middle East, with new opportunities opening in Central Asia.